2007
DOI: 10.1159/000108931
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the G34R Mutation in the 5 Alpha Reductase 2 Gene by Allele Specific PCR and Its Linkage to the 89L Allele among Egyptian Cases

Abstract: The 5 alpha-reductase type 2 deficiency is an autosomal recessive disorder of sexual development among 46,XY individuals. In Egypt, there is a prevalence of a G34R disease underlying mutation. This study aimed to devise a rapid diagnostic method based on allele specific PCR (AS-PCR) and a linked polymorphism (V89L). The results showed that one set of primers was capable to differentiate between normal, heterozygous, and affected individuals efficiently. All 34R mutation carrying sequences had 100% linkage to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Other studies in the Middle East, Italy, and Turkey had explored 46XY DSD from different prespectives and reported more or less similar etiology with little variations from our spectrum (7,(30)(31)(32)(33). The expression of the 5-α-reductase iso-enzyme 2 was shown by some molecular studies, as well as some common mutations such as in steroidogenic factor 1 (SF1, NR5A1) and G34R in Egyption patients with 46XY DSD (30,31). A first report of an Italian population emphasized the importance of differential diagnoses in patients with undervirilization.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Other studies in the Middle East, Italy, and Turkey had explored 46XY DSD from different prespectives and reported more or less similar etiology with little variations from our spectrum (7,(30)(31)(32)(33). The expression of the 5-α-reductase iso-enzyme 2 was shown by some molecular studies, as well as some common mutations such as in steroidogenic factor 1 (SF1, NR5A1) and G34R in Egyption patients with 46XY DSD (30,31). A first report of an Italian population emphasized the importance of differential diagnoses in patients with undervirilization.…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, similar to our observation, they found that there were delays in case referrals due to lack of awareness and sociocultural reasons (3). Other studies in the Middle East, Italy, and Turkey had explored 46XY DSD from different prespectives and reported more or less similar etiology with little variations from our spectrum (7,(30)(31)(32)(33). The expression of the 5-α-reductase iso-enzyme 2 was shown by some molecular studies, as well as some common mutations such as in steroidogenic factor 1 (SF1, NR5A1) and G34R in Egyption patients with 46XY DSD (30,31).…”
Section: Discussionmentioning
confidence: 52%
“…In this cohort, 18 different mutations were identified in the SRD5A2 gene, likely ruling out in our country the ancestor effect reported in other Mediterranean populations [Mazen et al, 2003;Skordis et al, 2005;Gad et al, 2007]. Regarding the new mutation, in silico predictions indicated an affected function of the mutated enzyme for the p.Val124Asp mutation.…”
Section: Molecular Geneticsmentioning
confidence: 58%
“…Most of them are missense mutations, but premature stop codons and small deletions have been shown, too. Specific mutations have been described in some ethnic groups, for example G34R among Egyptians [Mazen et al, 2003;Gad et al, 2007] and P212R among Mexican-Mestizo patients [Vilchis et al, 2010]. With the exception of a single report of uniparental disomy [Chávez et al, 2000], most individuals with 5α-reductase 2 deficiency are homozygous ( ∼ 65%) or compound heterozygous ( ∼ 35%) for loss-of-function mutations [Wilson et al, 1993;Wigley et al, 1994;Vilchis et al, 2008Vilchis et al, , 2010Cheon, 2011;Maimoun et al, 2011].…”
mentioning
confidence: 99%
“…In many developing societies, female infertility precludes marriage, which also affects employment prospects, and this drives the DSD patient's family to choose the male sex. Indeed, several studies have indicated the preference of the male sex of rearing despite the severity of genital ambiguity [83,96,97] . Furthermore in some traditional communities, parents feel that their child's condition is spiritual rather than medical and do not seek detailed clinical evaluation of the condition [98] .…”
Section: Discussionmentioning
confidence: 99%